Examining public perceptions and concerns about the impact of heatwaves on health outcomes using Twitter data - Safa Elkefi, PhD; Achraf Tounsi, PhD (Elsevier, 2024)
Background: Heat is becoming a global public health concern. This paper presents a comprehensive Twitter data analysis (2011-2023) to gain insights into public perceptions of heatwaves and their health-related concerns. Methods: A number (N = 2,070,197) of filtered tweets were included for analysis after preprocessing. Utilizing the Extractor of Demographic Characteristics (EDC) module, we extracted demographic attributes, including user type, gender, and age, highlighting the diverse voices in the Twitter conversation. Sentiment and emotional analyses were conducted utilizing BERT models. An active learning content analysis approach was employed using the GPT-3 model to identify health outcomes and concerns related to heat waves. Results: Our results show that joy and anger were the dominant emotions, reflecting positive and negative sentiments surrounding heat waves. Public sentiment varied, revealing concern and optimism in response to changing weather patterns.In terms of health outcomes, the paper categorizes and analyzes a wide range of concerns during heat waves, from heat-related illnesses to mental health issues. These findings provide valuable insights into how different health concerns are distributed across gender, user type, and age categories. An overview of the measures people took to control these issues was also given. Conclusions: This study illustrates the evolving dynamics of public emotional responses to heat waves, offering a holistic view of the various health-related concerns raised by the public during these extreme weather events. Such insights are essential for informing public health strategies and emergency responses to mitigate the adverse effects of heat waves and protect vulnerable populations.